Epicardial fat and incident heart failure with preserved ejection fraction in patients with coronary artery disease. (15th June 2022) - Mahabadi, Amir A.; Anapliotis, Viktoria; Dykun, Iryna; Hendricks, Stefanie; Al-Rashid, Fadi; Lüdike, Peter; Totzeck, Matthias; Rassaf, Tienush
Abstract: Background: We aimed to determine, whether epicardial adipose tissue (EAT) as local source of inflammation, as well as its change over time, associates with the development of heart failure with preserved ejection fraction (HFpEF) in patients with coronary artery disease. Methods and results: We retrospectively included 379patients (aged 65.2 ± 11.7 years, 70.2%male) with coronary artery disease but without heart failure at baseline, undergoing clinical and echocardiographic assessment in 2010–2013 and receiving a second assessment in 2014–2018. EAT thickness was defined as space between the myocardium and the pericardium and indexed (EATi) by body surface area. Change in EATi was calculated as the difference of follow-up and baseline EATi. HFpEF was defined according to presence of dyspnea, elevated natriuretic peptides, and structural and/or functional alterations on echocardiography in accordance with current European Society of Cardiology guidelines. During a median follow-up of 4.3 years, 142patients (37.5%) developed HFpEF. Patients with onset of HFpEF had higher EATi at baseline (2.4 ± 1.3 vs. 1.9 ± 0.9 mm/m 2, p = 0.001). In multivariable regression analysis, EATi associated with onset of HFpEF (1.25 [1.01–1.54], p = 0.04). Likewise, an increase in EATi over time was linked HFpEF development, independent of other risk factors and baseline EATi (1.39 [1.04–1.87], p = 0.03). EATi was significantly associated with follow-up b-type natriuretic peptide (BNP) levels (4.31[0.58–8.05], p = 0.024), but not with baseline BNP (2.24[−0.27–4.76], p = 0.08). Conclusion: EATi is associated with the development of HFpEF. The finding of changes in EATi altering the risk of HFpEF manifestation support the rationale for further research on epicardial fat modulation as a treatment target for HFpEF. Highlights: Epicardial adipose tissue is associated with the development of HFpEF. Changes in epicardial adipose tissue modulate the risk of HFpEF development. Epicardial adipose tissue may qualify as potential treatment target in HFpEF.